Effects of ownership structure and proprietary cost on forward looking information disclosure and its impact on firm performance - Noghondari, Ali Taebi (2012)
The focus of this study is to investigate the relationship between ownership structure, namely family ownership, institutional ownership, government ownership and diffused ownership, and the extent of forward looking information disclosure of public listed companies in Malaysia. The association between the proprietary cost of the firms and the extent of forward looking information disclosure is also examined. This study then examines whether the extent of forward looking information disclosure impacts firm market performance. This study used profitability and industry type as control variables. Content analysis was applied to measure the extent of forward looking information disclosure. The type of ownership structure was determined by the percentage of shares held by the top five share-holders. Relative market share was used as a proxy for proprietary cost. Finally, corporate market performance was measured by three indicators volatility of stock return, market liquidity ratio and Tobin’s Q. The sample consisted of 80 companies drawn from the 100 largest public-listed companies based on market capitalization at the end of 2009. Multiple regression analyses were carried out to examine the relationships among ownership structure, proprietary cost and the extent of voluntary disclosure of forward looking information. Simple linear regression was used to determine the relationship between the extent of forward looking information disclosure and firm market performance. The results show that among the ownership structure types, only family ownership has a significant negative effect on the extent of forward looking information disclosure. Although the proprietary cost significantly influences the extent of forward looking information disclosure, the direction is positive which is not as hypothesized. In addition, the extent of voluntary disclosure of forward looking information is positively related to the firm’s market performance. Empirical evidence provided in this study may be useful to practising managers. Corporate management may improve their firm’s market performance by disclosing more forward looking information about their future prospects. The result of this study may be also helpful to regulators in Malaysian capital market in formulating information disclosure policy to promote transparency and to improve quality of information disclosure in annual reports to enhance market confidence.